2020
DOI: 10.1158/1078-0432.ccr-20-1764
|View full text |Cite|
|
Sign up to set email alerts
|

A Phase II Study of Abemaciclib in Patients with Brain Metastases Secondary to Hormone Receptor–Positive Breast Cancer

Abstract: The primary objective was to evaluate intracranial objective response rate (iORR) in patients receiving abemaciclib with brain or leptomeningeal metastases (LM) secondary to hormone receptor-positive (HR þ) metastatic breast cancer (MBC). Secondary objectives evaluated extracranial response, abemaciclib pharmacokinetics, brain metastases tissue exposure, and safety. Patients and Methods: This nonrandomized, phase II study (NCT02308020) enrolled patients in tumor subtype-specific cohorts AD: A (HR þ , HER2 À MB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 35 publications
1
103
0
Order By: Relevance
“…Also, in the setting of ABC, metastatic CNS disease has historically been excluded from most clinical trials. This reality is changing, and in recent years trials have been designed to specifically approach CNS metastasis [55,65], some of them, in particular those in HER2+ disease [66,67], with promising results. Despite this, LMD continues to be understudied, and evidence for optimal treatment in BC-LMD is still limited [67].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the setting of ABC, metastatic CNS disease has historically been excluded from most clinical trials. This reality is changing, and in recent years trials have been designed to specifically approach CNS metastasis [55,65], some of them, in particular those in HER2+ disease [66,67], with promising results. Despite this, LMD continues to be understudied, and evidence for optimal treatment in BC-LMD is still limited [67].…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup of 8 patients in this study had surgical resection of BM while undergoing treatment, and it was shown in the resected samples that therapeutic levels of abemaciclib were reached in BM, demonstrating abemaciclib and its active metabolites penetrated the BBB. 89 For patients with triple-negative BCBM, two chemotherapy regimens seem to show specific CNS activity: the anti-vascular endothelial growth factor agent bevacizumab plus paclitaxel in a small Phase 2 study (70% ORR but only 6 patients with triplenegative MBC) 90 and the microtubule inhibitor eribulin in case reports. 91 A Phase 2 trial presented at ASCO 2013 highlighted a combination of bevacizumab plus carboplatin in the treatment of BCBM.…”
Section: Trastuzumab-based Regimens For Patients With Her2 + Bmmentioning
confidence: 99%
“…To date, a small number of clinical trials have been reported specifically studying systemic treatments for breast cancer, lung cancer, and melanoma LM [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ], a small subset of which were randomized studies [ 71 , 72 , 73 , 75 , 89 , 90 ]. Several of these studies employ an intrathecal administration of chemotherapy, meaning that the agents are injected directly into the CSF.…”
Section: Treatment Approaches For Lmmentioning
confidence: 99%
“…A systemic treatment with small-molecule targeted agents also plays an important role in the management of LM. These therapies include the standard targeted agents used for a particular tumor type defined by specific molecular features, such as abemaciclib (ER+) and trastuzumab (HER2+) for breast cancer LM, EGFR inhibitors in EGFR mutant lung cancer LM, and BRAF + MEK inhibition in BRAF mutant melanoma LM [ 51 , 83 ]. Most recently, the third-generation mutant EGFR inhibitor, osimertinib, has shown substantial activity in controlling LM from the EGFR mutant lung cancer [ 78 ].…”
Section: Treatment Approaches For Lmmentioning
confidence: 99%